2004
DOI: 10.1038/sj.bmt.1704360
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and osteonecrosis in survivors of childhood allogeneic bone marrow transplantation

Abstract: Summary:Our purpose was to evaluate frequency and severity of bone mineral decrements and frequency of osteonecrosis in survivors of pediatric allogeneic bone marrow transplantation (alloBMT). We retrospectively reviewed demographic information, treatment, magnetic resonance (MR) imaging studies (hips and knees), and bone mineral density (BMD) studies of 48 patients as measured by quantitative computed tomography (QCT). In all, 24 patients were male; 37 were Caucasian. Median age at alloBMT was 10.3 years (1.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 44 publications
4
88
2
Order By: Relevance
“…Quantitative computed tomography enables measurement of the 'true' BMD. Kaste et al 13 measured vertebral BMD by quantitative computed tomography in 43 patients with a median of 5.1 years after allo-SCT in childhood and found that 11 patients had osteopenia and nine patients had osteoporosis (thus 47% had osteopenia or osteoporosis), that is, indeed higher prevalence numbers than in studies using areal BMD, including the present one. Another limitation of the present study is the rather small sample size, which restricts statistical power.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Quantitative computed tomography enables measurement of the 'true' BMD. Kaste et al 13 measured vertebral BMD by quantitative computed tomography in 43 patients with a median of 5.1 years after allo-SCT in childhood and found that 11 patients had osteopenia and nine patients had osteoporosis (thus 47% had osteopenia or osteoporosis), that is, indeed higher prevalence numbers than in studies using areal BMD, including the present one. Another limitation of the present study is the rather small sample size, which restricts statistical power.…”
Section: Discussioncontrasting
confidence: 47%
“…5,[11][12][13][14] We present a study of areal BMD after SCT that constitutes the longest follow-up published to date (median 18.2 years) and in which all patients had reached final height. BMD total BMD femneck and BMD totalhip were significantly lower among the patients compared with the controls, but there was no significant difference in BMD lumbar This is consistent with data showing a preferential recovery of BMD in the lumbar spine after SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Pediatric BMT survivors have decreased bone mineral density and are at higher risk of fracture, osteonecrosis and osteoporosis (particularly females). [50][51][52][53][54] Avascular necrosis of bone occurs in more than 10% of BMT survivors. 54 Endocrine arrest of bone development refers to the decreased growth in childhood BMT survivors due to BMT conditioning and GVHD treatment.…”
Section: Psychological Healthmentioning
confidence: 99%
“…6 It has been described after hematopoietic stem cell transplantation (SCT) as well, with the majority of cases reported in alloSCT recipients. [7][8][9][11][12][13][14][15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35] AlloSCT-associated BMD loss is usually described in the first 6-12 months after the transplantation, but varies widely from 40 days 17 to 4-6 years after the transplantation, 30,31,34 and in some instances can persist for 10-12 years. 26,28 Baseline BMD pre-SCT is usually within the normal limits; [15][16][17]24,[27][28][29][30]33 the few exceptions noting high O/O prevalence pre-SCT are probably due to the underlying diseases or intensive chemotherapy prior to the transplantation.…”
Section: Introductionmentioning
confidence: 99%